2015
DOI: 10.1007/s10853-015-9156-0
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal crystallization kinetics and melting behavior of poly(l-lactic acid)/WS2 inorganic nanotube nanocomposites

Abstract: Environmentally friendly and biocompatible tungsten disulphide inorganic nanotubes (INT-WS 2 ) were introduced into a poly(L-lactic acid) biopolymer matrix to generate novel nanocomposite materials through an advantageous melt-processing route. The effects of INT-WS 2 on isothermal crystallization and melting behaviour of PLLA have been investigated. INT-WS 2 has excellent acceleration effectiveness on the melt-crystallization of PLLA better than the promising nano-sized fillers reported in the literature (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Equation (2) can be rewritten as:logfalse[lnfalse(1Xfalse(tfalse)false)false]=logk+nlogt and the values of log [−ln(1 − X ( t ))] plotted versus log t , allowing the Avrami exponent n and the crystallization rate constant k to be calculated from the slope and intercept of the linear fit, respectively. It is rare that the Avarmi equation can be used to describe the entire crystallization process, but is widely accepted as valid at the early stage of crystallization, as previously reported in our studies for nylon-6/IF-WS 2 [21] and PLLA/INT-WS 2 [25]. Linear regressions of these straight lines at low levels of crystalline transformation (5–40%) yielded the Avrami exponents ( n ) shown in Table 1.…”
Section: Resultssupporting
confidence: 63%
“…Equation (2) can be rewritten as:logfalse[lnfalse(1Xfalse(tfalse)false)false]=logk+nlogt and the values of log [−ln(1 − X ( t ))] plotted versus log t , allowing the Avrami exponent n and the crystallization rate constant k to be calculated from the slope and intercept of the linear fit, respectively. It is rare that the Avarmi equation can be used to describe the entire crystallization process, but is widely accepted as valid at the early stage of crystallization, as previously reported in our studies for nylon-6/IF-WS 2 [21] and PLLA/INT-WS 2 [25]. Linear regressions of these straight lines at low levels of crystalline transformation (5–40%) yielded the Avrami exponents ( n ) shown in Table 1.…”
Section: Resultssupporting
confidence: 63%
“…The intensity ratio I peak /I valley is constant for the amorphous UNST films, but after stretching (ST0) it increases with the concentration of nanotubes first slowly up to 0.2 wt% and then with a sudden jump at 0.3 wt%, remaining almost constant the final concentration of 0.6 wt%. While the stretching itself does not induce noticeable crystallization in PLA (ST0, WS 2 = 0 wt%) (but probably just a chain alignment), the nanotubes promote crystallization by acting as nucleation agents [23]. The value of I peak /I valley for the conditions ST3 and ST10 is very similar to and larger than the corresponding ST0 value.…”
Section: Resultsmentioning
confidence: 82%
“…Despite these advantages, to the best of our knowledge, only a few studies are reported in literature on PLA-WS 2 nanocomposites, mainly focused on thermal properties of samples obtained by melt-mixing [21][22][23][24][25]. These studies show that WS 2 NTs remarkably influence the kinetics of nucleation and growth of the PLA during the cold crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…However, improving the crystallinity is often not effective if only the temperature gradient and cooling rate are controlled, and the temperature cannot be controlled easily in real manufacturing. The final and maybe the most promising approach is to add some organic and/or inorganic particles as nucleating agents to the PLLA matrix, such as sodium stearate [30], nano-clays [31], graphite particles [32], triclosan nanoparticles [33], tungsten disulphide inorganic nanotubes (INT-WS 2 ) [34], or magnesium oxide nanoparticles [35]. Compounding with these particles by physical blending is a conventional method of fabricating PLLA composites and was proved to be convenient to improve the crystallization behavior of PLLA.…”
Section: Introductionmentioning
confidence: 99%